Muslim women and knowledge: Are we ready to face the ‘Fourth Industrial Revolution’? - Mohd Yunus, Raudah; Hasan, Md. Mahmudul (About Islam, 2016)
The journey and achievements of the classic Islamic civilization as documented in history therefore had nothing to do with the rejection of religion or the complex battle between religion and rationality as experienced by the west. Conversely, its very basis of knowledge system was supported by the teachings of its holy book, and was derived from a call to respect the ‘law of nature’.